Online Islamic business enhancer tool (OIBET) for young entrepreneurs - Hassan R.; Mahinderjit-Singh M.; Hassan H.; Yuhaniz S.S. (International Business Information Management Association, IBIMA, 2023)
Developing countries; Information management; International trade; Sales; Websites; Entrepreneurial skills; Entrepreneurship; Government; Government institutions; International markets; M-commerce; Plug; Product information; Electronic commerce